Lasiodiplactone A, a novel lactone from the mangrove endophytic fungus Lasiodiplodia theobromae ZJ-HQ1. Issue 30 (21st July 2017) - Chen, Senhua; Liu, Zhaoming; Liu, Hongju; Long, Yuhua; Chen, Dongni; Lu, Yongjun; She, Zhigang
Abstract : Lasiodiplactone A (1 ), an unprecedented lactone, was obtained from the mangrove endophytic fungus Lasiodiplodia theobromae ZJ-HQ1. Abstract : Lasiodiplactone A (1 ), an unprecedented lactone, was obtained from the mangrove endophytic fungus Lasiodiplodia theobromae ZJ-HQ1. The structure of1 was established by analysis of NMR spectroscopic data and electronic circular dichroism (ECD) spectra. Lasiodiplactone A (1 ) was the first example of lactone that possesses a unique tetracyclic system (12/6/6/5) of RAL12 (12-membered β-resorcylic acid lactone) with a pyran ring and a furan ring. A possible biogenetic pathway for1 was proposed. Compound1 showed anti-inflammatory activity by inhibiting nitric oxide (NO) production in lipopolysaccharide activated in RAW264.7 cells with IC50 value of 23.5 μM and exhibited potential α-glucosidase inhibitory activity with IC50 values of 29.4 μM.